In the Midst of Madness: Mental Health Literacy as Null to Explicit Curriculum in Public Spaces - Rondeau-Madrid , Erin (Journal of Public Pedagogies, 2022)
In the wake of school closings due to COVID-19, public agencies and media have been increasingly relegated to the role of educator across publics. The promotion of mental health literacy has moved from null curriculum to explicit, as public agencies have pushed the narrative of an unprecedented mental health crisis, despite the crisis having been evident pre-pandemic. This text questions the motivations of increased mental health literacy campaigns across agencies and publics, recognizing that those with vested interests in keeping the neoliberal system intact lend little help to the most vulnerable populations.